ALGORITHM C4.5 IN CLASSIFYING HEALTH OF CAT - NURLINDASARI TAMSIR (Journal of Information Technology and Its Utilization, 2021)
One of the activities in the TIU (Technical Implementing Unit) of Office of Animal Husbandry and Animal Health is to carry out the examination of pet health, record and issue an Animal Health Certificate (AHC). The object in this research was cat, where the examination was still performed by laboratory test, using paper as a form of diagnosis carried out by a vet and not using the technology. Therefore, an application to provide decision in determining healthy cat that also implements the algorithm C4.5 based on android system was designed. This system was able to perform diagnosis of cat diseases quickly based on previous medical record, with a training history (training data) as many as 44 cases. Then the classification process would strengthen the results of cat disease diagnosis such as how to deal with disease that had similar symptoms so as to facilitate the Office of Animal Husbandry and Animal Health, as a comparison to issue an Animal Health Certificate. Based on the Black Box testing, the functionality of the module was in accordance with the needs of the system, while the accuracy testing generated the percentage value of 93.18%. This shows that the algorithm C4.5 has a good accuracy to determine healthy cat.